Two Cases of Human T-Lymphotropic Virus Type I-Associated Myelopathy/Tropical Spastic Paraparesis Caused by Living-Donor Renal Transplantation - Yasutaka Tajima; Mariko Matsumura; Hiroaki Yaguchi; Yasunori Mito (Case Reports in Neurological Medicine)
In rare instances, recipients of organ transplants from human T-lymphotropic virus type I- (HTLV-I-) positive donors reportedly developed neurologic symptoms due to HTLV-I-associated myelopathy (HAM). We present herein two cases of HAM associated with renal transplantation from HTLV-I seropositive living-donors. The first patient was a 42-year-old woman with chronic renal failure for twelve years and seronegative for HTLV-I. She underwent renal transplantation with her HTLV-I seropositive mother as the donor, and she developed HAM three years after the transplantation. The second patient was a 65-year-old man who had been suffering from diabetic nephropathy. He was seronegative for HTLV-I and underwent renal transplantation one year previously, with his HTLV-I seropositive wife as the donor. He developed HAM eight months after renal transplantation. Both cases showed neurological improvements after the immunomodulating therapies. We tried to shed some light on the understanding of immunological mechanisms of transplantation-associated HAM, focusing on therapeutic strategies based on the immunopathogenesis of the condition.